ANALYSIS OF MORPHOLOGICAL PECULIARITIES OF THE STATE AREA OF THE REPUBLIC OF KAZAKHSTAN - R.A. Karatabanov; K.V. Dzhanaleeva; A.V. Krotov (Academic Journal of Physical and Chemical Sciences, 2019)
In modern conditions, space and location are not only considered to be the second category of public policy and become an important factor in the socio-economic development of the country. The main purpose of this article is to provide a comprehensive geographical analysis of the morphological features of the state territory of Kazakhstan to ensure geopolitical security of the country. Authors calculate the compactness index of the state territory of the country and the functional level of the capital, defines the geographical environment of the Republic of Kazakhstan. The results of the analysis allow to determine the advantages and disadvantages of morphological features of the state territory for the purpose of taking comprehensive measures for its strengthening and development.